The Effect Of Five Dimensions Of Quality Of Public Services Against Public Satisfaction Levels In Sub Ompo District Of Lalabata Soppeng Regency - Hasnih -; Hasmin Tamsah (Jurnal Mirai Management, 2016)
Abstract This study aims to: determine the effect of service quality on satisfaction of the people in the village office Ompo District of Lalabata Soppeng Regency. This research was conducted at the office of the District Urban Village Ompo Village of Lalabata District Soppeng Regency is located at Jalan Lawo No. 01 Soppeng. While the time will be used in this study for 2 months starting in November and December 2016. This research population is the number of residents registered as a community to get service at the Village Office Ompo 2015 which amounted to 290 people The results of this study explains that there is a positive influence between the physical evidence, reliability, responsiveness and assurance of the satisfaction of the people, whereas empathy variable has no significant effect on satisfaction Ompo Village community. Test results obtained by the value of the coefficient of determination adjusted R-square is 0.793. This shows of community satisfaction is influenced by a combination of the five independent variables, physical evidence (tangible), reliability (reliability), responsiveness (responsiveness), assurance (assurance) and empathy (empathy). The result of the calculation of the t-test is known that from the variable Responsiveness (X3) obtained by value Ompo Village community. arithmetic amounted can be concluded that there is positive and significant correlation between responsiveness to community satisfaction village Ompo, it is also clear that of the five independent variables, responsiveness (X3) is a variable that provides a dominant influence on satisfaction Keywords: physical evidence, Reliability, Responsiveness, Assurance, Empathy and community satisfaction